2016
DOI: 10.1155/2016/9816461
|View full text |Cite
|
Sign up to set email alerts
|

A pH-Sensitive Injectable Nanoparticle Composite Hydrogel for Anticancer Drug Delivery

Abstract: According to previous reports, low pH-triggered nanoparticles were considered to be excellent carriers for anticancer drug delivery, for the reason that they could trigger encapsulated drug release at mild acid environment of tumor. Herein, an acid-sensitiveβ-cyclodextrin derivative, namely, acetalated-β-cyclodextrin (Ac-β-CD), was synthesized by acetonation and fabricated to nanoparticles through single oil-in-water (o/w) emulsion technique. At the same time, camptothecin (CPT), a hydrophobic anticancer drug,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…In vitro cumulative drug release of CQ and PG from hydrogels revealed that the hydrogels had the capacity to retain a substantial amount of drug in simulated gastric juice condition. Similar findings were reported by some researchers [35,36]. The solubility of the drugs influenced their release rate from the hydrogels; Castro et al [19] and Alhnan et al reported similar findings [37].…”
Section: Discussionsupporting
confidence: 84%
“…In vitro cumulative drug release of CQ and PG from hydrogels revealed that the hydrogels had the capacity to retain a substantial amount of drug in simulated gastric juice condition. Similar findings were reported by some researchers [35,36]. The solubility of the drugs influenced their release rate from the hydrogels; Castro et al [19] and Alhnan et al reported similar findings [37].…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, graphene is used as nanoscale building blocks for new nanocomposites because of its unique properties [12][13][14]. Recent research showed that magnetic nanoparticles (MNPs) could be attached to graphene, which can be applied in magnetic resonance imaging [15], targeted drug delivery [16,17], biocompatible adsorbent [18], magnetic solid phase extraction [19], microwave electromagnetic [20], Schottky diode applications [21], and biomolecule immobilization [22].…”
Section: Introductionmentioning
confidence: 99%
“…A hydrogel with a DNA backbone permitted tethering of DNA-functionalized AuNP via complementary base pair binding; upon irradiation at the AuNP SPR, the DNA cross-link melts releasing the AuNP and any encapsulated drug [48]. Additional composite hydrogels have been similarly created to be sensitive to pH, which is particularly important within the tumor microenvironment [49].…”
Section: Nanoparticle-hydrogel Compositesmentioning
confidence: 99%